Access to Maternal Healthcare in Rural Bangladesh: A literature-based Analysis on Factors Affecting Maternal Healthcare Utilization in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2021)
In the last decade, Bangladesh has made substantial improvements of maternal and newborn mortality, such the maternal mortality ratio (MMR) had dropped from 574 per thousand live births in 1990 to 170 per thousand live births in 2013. Despite these improvements, Bangladesh is still lagging in achieving equity in service utilization. Literature manifested significant healthcare inequities across different socio-demographic factors and religious and cultural views. The primary aims of this analysis are – i) to assess the disparities in the quality and availability of maternal healthcare in Bangladesh and its relation to the service utilization in rural Bangladesh, ii) to identify demand-side interventions implemented in developing countries and relevant considerations to promote maternal healthcare utilization in rural Bangladesh. A narrative literature review was conducted using Rudolph Matas Library, Tulane University online resources, Google Scholar and PUBMED. Articles published between January 1st, 2015 and December 31st, 2018 describing quality, availability and  utilization of maternal healthcare services; existing disparities and barriers in healthcare utilization in rural Bangladesh are included in the analysis. This analysis also includes articles describing the impact of demand-side interventions on healthcare utilization in developing countries. A total of 10 articles met the selection criteria. Bibliographies of selected articles were also searched to include additional information in this analysis. Reviews of the literature revealed a significant healthcare equity gap according to place of residences, wealth status, age at birth, and parity of mothers in Bangladesh. According to available study findings, the level of mothers’ education, cultural and social views, women’s employment status, distance of health facility, and perceived quality of care act as significant factors influencing maternal healthcare utilization in rural Bangladesh. Studies have shown that demand-side interventions considering cultural context and other existing barriers result in improved uptake of maternal healthcare and improved health outcome. Only availability of services cannot translate into better outcomes, unless those services are of acceptable quality and the population irrespective of their socio-demographic status can attain those services without any perceived barrier. The analysis suggested, along with ensuring availability and quality of healthcare, the need for demand-side interventions addressing existing barriers make services accessible to the rural communities in Bangladesh.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 848